The Effect of Short-term Use of Chamomile Essence on Muscle Soreness in Young Girls after an Exhaustive Exercise - M Khatami Sabzevar; AH Haghighi; R Askari (Institue of Medicinal Plants, ACECR, 2017)
Background: Intensive physical activity can lead to muscle soreness. Objective: Evaluate the effect of short-term use of of chamomile essence (CE) on muscle soreness in young girls after an exhaustive exercise. Methods: Twenty young girls volunteered. They were randomly assigned into two equal groups of experimental and control. The experimental group drank 300 ml of CE twice daily for twelve days. The control group drank water and the chamomile essential oil as placebo during this period. In the eleventh day, exhaustive exercise on a treadmill with a negative slope of 5 degrees for all subjects was conducted. Blood samples were taken on the first and tenth days before the exhaustive exercise, and 1, 24 and 48 hours after exercise. Data were analyzed using independent t-test and ANOVA for repeated measure with a significant level of P<0.05. Results: No significant difference was detected between the two groups in the index of serum creatine kinase. Lactate dehydrogenase index in 1 and 48 hours after the test in the experimental group was significantly decreased compared with the control group. Aspartate amino transferase index in the experimental group increased 24 hours after the exercise, and decreased after 48 hours of the exhaustive exercise compared to the control group. Pain scale in the experimental group was reduced 1 and 24 hours after the test compared with the control group. Conclusion: The results suggested that young girls who want to do exhaustive exercises can drink CE to prevent or reduce the effects of muscle soreness.